Heavy Metal Zinc (Zn) in Sediments and Roots of Mangrove Sonneratia Alba and Avicennia Marina Analysis Using Geographic Information System (Gis) at Blekok Village Ecotourism Beach, Situbondo, East Java, Indonesia - Zakiyah, Umi; Wardani, Alifya Nurul; Erintika, Dista (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2024)
The Kampung Blekok Ecotourism Beach in Situbondo, which features a mangrove ecosystem with key species such as Sonneratia alba and Avicennia marina, is surrounded by various human and natural activities, making it vulnerable to heavy metal pollution such as zinc (Zn). Mangroves play a crucial role in coping with this contamination. The purposes of this study were analyzing the concentration of heavy metal Zn found in the sediment and roots of the mangroves Sonneratia alba and Avicennia marina, and the distribution of heavy metal Zn in the mangrove sediments of Sonneratia alba and Avicennia marina, as well assessing the ability of the mangrove roots of Sonneratia alba and Avicennia marina in accumulating heavy metal Zn. This research used a survey method. The results indicated that the concentration of heavy metal Zn in the mangrove sediment of Sonneratia alba ranges between 0.7431-0.8412 ppm, while in the roots of Sonneratia alba, it ranges between 0.5472-0.7255 ppm. The concentration of heavy metal Zn in the sediment of Avicennia marina ranges between 0.7699-0.8782 ppm, while in the roots of Avicennia marina, it ranges between 0.5884-0.7194 ppm. According to the standards issued by NOAA, ANZECC, and USEPA, the concentration of heavy metal Zn in the sediment is still considered safe because it does not exceed the established quality standards. The Bioconcentration Factor (BCF) or absorption capacity of the mangrove roots of Sonneratia alba ranges between 0.724-0.8624 ppm, while for Avicennia marina, it ranges between 0.7309-0.8407 ppm. The BCF values in both mangroves indicated that both were excluders. Statistical tests show that there was no significant difference between the abilities of the two types of mangroves to accumulate heavy metal Zn. The map results based on IDW interpolation on the sediment of Sonneratia alba are shown with a dark gradient indicating the highest Zn concentration at stations 5 and 6, while the lightest gradient indicating the lowest concentration at station 1. The distribution of heavy metal Zn concentration in the mangrove sediment of Avicennia marina is shown with a dark gradient at station 6 and a light gradient at station 2.